1990
DOI: 10.1017/s0272263100008743
|View full text |Cite
|
Sign up to set email alerts
|

What You Don't Know Can't Help You

Abstract: A number of recent studies in L1 listening comprehension have shown that background knowledge plays a crucial role in the comprehension process. The purpose of the present article is threefold: (a) to review the literature on background knowledge, (b) to present the findings of pertinent L1 and L2 research, and (c) to report the results of a preliminary study of L2 listening comprehension and background knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…In addition, the subjects in general performed better on passage-independent items in the test of the familiar topic, showing a significant interaction between prior knowledge (in terms of familiarity of topic) and test type (passage-dependent and passageindependent). Long's (1990) study of learners of Spanish as a Foreign Language corroborated these results. Subjects were given a summary task after listening to the taped lectures, one familiar and one unfamiliar in terms of cultural themes.…”
Section: Literature Reviewsupporting
confidence: 56%
“…In addition, the subjects in general performed better on passage-independent items in the test of the familiar topic, showing a significant interaction between prior knowledge (in terms of familiarity of topic) and test type (passage-dependent and passageindependent). Long's (1990) study of learners of Spanish as a Foreign Language corroborated these results. Subjects were given a summary task after listening to the taped lectures, one familiar and one unfamiliar in terms of cultural themes.…”
Section: Literature Reviewsupporting
confidence: 56%
“…For the analysis of L2 listening in natural situations, however, it is far from directly applicable. On the other hand, there are claims that most important of all in the L2 situation is the use of context; efficient use of context enables L2 listeners to compensate for imperfections in lower-level processing (e.g., Chiang and Dunkel, 1992;Long, 1990). This too is an important research topic (indeed, not only in L2 listening); but this too fails to provide a useful analysis of L2 listening and its problems.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have shown intermediate and lower intermediate learners rely heavily on bottom-up processing, breaking down the sound stream into meaningful units, for interpreting the incoming speech stream (Hansen & Jensen, 1994), many more have shown top-down processing, drawing on the context and background knowledge, is widely used (Mueller, 1980;Voss, 1984;Wolff, 1987;Koster, 1987;Mack, 1988;Long, 1989) and that it could be misleading if learners failed to correct their initial predictions based on their background knowledge in a timely fashion (Long, 1990;Lund, 1991;Hansen & Jensen, 1994;Tsui & Fullilove, 1998). However, more recent studies have underlined that, depending on the circumstance, one or the other strategy might be brought to the front and this may well be different from learner to learner (Field, 2004).…”
Section: A Results Analysis Of 11 Test D'évaluation De Français (Tef) mentioning
confidence: 99%